Pilihan Bahasa Generasi Muda di Destinasi Wisata di Bali - Ni Luh Nyoman Seri Malini; Ni Luh Putu Laksminy; I Nengah Ketut Sulibra (Pusat Kajian Bali Universitas Udayana, 2018)
Bali is one of the tourist destinations in Indonesia. Among areas that are frequently visited by the tourists are, Kuta, Sanur, and Ubud. For that reasons, many people in the regions participate in the tourism activities. It cannot be denied that many languages are involved in the areas so that the society of the parts becomes bilinguals or even multilingual. Based on such linguistic situation, this study aims at nding language use and choice in family, neighbor, education and religion domains.The data were in the form of spoken data collected from young people at di erent tourist destinations such as Sanur, Kuta, and Ubud. A qualitative method applied in this study. In spite of the facts, the result of the research shows that the Balinese language is still preferred as the means of communication among the young people both in a family, neighbor, and religious domains.